The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1590/s0100-83582002000300003
|View full text |Cite
|
Sign up to set email alerts
|

Ontogenia dos nectários extraflorais de Triumfetta semitriloba (tiliaceae)

Abstract: Triumfetta semitriloba é uma planta daninha que apresenta nectários florais e extraflorais, sendo os últimos visitados por formigas que protegem a planta do ataque de insetos. O presente trabalho teve como objetivo descrever a ontogenia dos nectários extraflorais de T. semitriloba. Para isso, amostras de nectários em quatro estádios de desenvolvimento foram obtidas de plantas adultas, sendo o material submetido às técnicas usuais de obtenção de lâminas permanentes. Os nectários iniciam o seu desenvolvimento pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
(31 reference statements)
2
3
0
4
Order By: Relevance
“…The characteristics of the secretory epidermis and nectariferous tissue observed in the nectary of S. biglandulosum match the description of structural extrafloral nectaries in other species as reported by several authors (Dave and Patel 1975;Elias and Gelband 1976;Fahn 1979;Metcalfe and Chalk 1979;Bentley and Elias 1983;Anderson and Symon 1985;Gaffal et al 1998;Freitas et al 2001;Paiva et al 2001;Leitão et al 2002;Rocha et al 2002;Thadeo et al 2008).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The characteristics of the secretory epidermis and nectariferous tissue observed in the nectary of S. biglandulosum match the description of structural extrafloral nectaries in other species as reported by several authors (Dave and Patel 1975;Elias and Gelband 1976;Fahn 1979;Metcalfe and Chalk 1979;Bentley and Elias 1983;Anderson and Symon 1985;Gaffal et al 1998;Freitas et al 2001;Paiva et al 2001;Leitão et al 2002;Rocha et al 2002;Thadeo et al 2008).…”
Section: Discussionsupporting
confidence: 87%
“…The pattern of development observed in the nectaries of S. biglandulosum was similar to what has been reported for extrafloral nectaries of other plant families (Arbo 1972;Dave and Patel 1975;Roshchina and Roshchina 1993;Silva and Machado 1999;Leitão et al 2002;Paiva and Machado 2006;Thadeo et al 2008). The asynchronous cellular divisions during the nectary ontogenesis are an ordinary process, as described for Pedilanthus tithymaloides, Euphorbiaceae (Dave and Patel 1975), and Triumfetta semitriloba, Tiliaceae (Leitão et al 2002).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Muitos autores têm ressaltado a importância das variações nas características dessas glândulas como ferramenta efi caz para estudos de sistemática em diferentes categorias taxonômicas, especialmente na família Leguminosae (Bhattacharyya & Marheshawari 1970a, 1970bMetcalfe & Chalk 1979;Leitão et al 2002;Bortoluzzi et al 2007;Morim & Barroso 2007).…”
Section: Introductionunclassified
“…The basal teeth glands located on the margins of the leaves and of the bract subtending the inflorescence of T. semitriloba are visited by ants (Sobrinho et al 2002). An anatomical and ontogenetic study on the foliar glands has been published (Leitão et al 2002), but no other references were found regarding the anatomy and the secretory product of these glands, including the floral nectaries.…”
Section: Introductionmentioning
confidence: 99%